PENGARUH PENAMBAHAN TRAKSI OSCILASI PADA TRANSCUTANEUS ELECTRICAL NERVE STIMULATION TERHADAP INTENSITAS NYERI PADA PENDERITA OSTEOARTHRITIS GENU - Isidorus Jehaman; Redi Tantangan (Jurnal Penelitian Keperawatan Medik, 2018)
Degenerative diseases are chronic chronic diseases that affect a person's quality of life and productivity. One of the most common degenerative diseases and which has a high mortality rate is osteoarthritis in the knee. The purpose of this study was to determine the differences in the administration of TENS with Oscillation Traction on pain intensity in patients with genital osteoarthritis in Grandmed Lubuk Pakam Hospital. Research Method: this is research is quasi-experimental while the research design uses pre-test and post-test. The sample of this study used 2 treatment groups, namely treatment group 1 using TENS and treatment group 2 using oscillation traction. Both sample groups measured pain scales using the verbal description scale. The results of the analysis of the influence test with Independent t-test in treatment group 1 and treatment group 2. Test paired sample t-test obtained p value = 0.001 (p 5 0.05), which means that there is a difference in pain intensity before and after being given TENS. Whereas in the treatment group 2 oscillation traction obtained results of p = 0.001 (.050.05) which means that there is a difference in pain intensity before and after being given oxyylation traction. From the results of the independent t-test in getting results with p = 0.000 (α<0.05) it can be concluded that there is a difference in the administration of TENS with oscillation traction against pain intensity in Genu Osteoarthtritis sufferers. Conclusion There is a Difference in Giving TENS with Oscillation Traction Against Pain Intensity in Genu Osteoarthtritis Patients. Suggestion: minimize activity overload the knee joint, squat up and down stairs or lift excessive weight.